Estudo de relações ecológicas em planícies hipersalinas (apicum) do estado do Ceará - Cabral, Raiana Lira (2015)
This study investigates ecological process and dynamic of the hypersaline tidal flats (HTF, locally knowns as “apicum”). The HTF systems are characterized by flat landscape and hypersaline soil conditions that may occour in arid and semiarid regions of the world. Usually HTF can be found inside mangrove forest or as a transitional system between mangrove and dry land ecosystem. These areas are highly important for advances of mangrove forest in case of sea level increase. Besides, HTF have great economic value, as prioritarian areas to install aquaculture or saline ponds. Also it represents security zones for traditional populations, as artisanal fishermen. However, the ecological process which drives the HTFs systems remain poorly knew. The studies presented in this doctoral dissertation aim to fulfill some lacks of knowledge about ecological process that could drive the HTF dynamic. The chapter 1 is a bibliographical review about this system. On chapter 2 were evaluated possibles mechanisms used by plants in order to improve their survival in such stressed environment through the study of rhizosphere soils and comparison with bulk soils. On chapter 3, through an experimental study in the field, the possible effect of two crab species bioturbation on HTFs soils and it possible effects on soil properties were evaluated. The chapter 4 registered the evaluation of ecological interactions among biotic and abiotic fractions of the system using ecological modeling tools. In this sense, a structural ecological model was designed using microrelief elevation, soil properties, two plant species biomass and the covering areas of two crab species. Based on results obtained in these studies, it was possible to conclude that HTFs have a particular ecological dynamic and have close relation with mangrove forests due the nutrients, material and animal population flux shared by them. The plant community of HTFs areas is componed mainly by pioneers’ clonal halophytes species. These species seemed to have different strategies to deal with saline stress, an important limitant factor for their growing and distribution. The seasonal effects were noteworthy mainly in bulk soils. In this sense, it is possible that plant estabilize the environment in their benefit. The crabs were able to affect biogeochemical dynamic in HTF soils. However, the burrouing effects of crab species on soil properties were different and seemed reflect the species habit. Although bioturbation effects were important, the modifications on HTF soil properties were less evident than in mangrove forests. Environmental process related to salinity and nutrients availability are among the main factors to drive crabs distribution and plant growth in HTFs. These processes were dependent of microrelief variation. A combination of abiotic factors (microrelief elevation and soil properties) and positive relations among plant species seems to guide the ecological dynamics in HTFs systems. Conservation strategies of coastal environments areas must include the HTF protection due their importance for coastal environments on climate change scenario and economic importance, but mainly because their unique ecological characteristics.